2007
DOI: 10.1177/1545968308315598
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Disturbance in Closed Head Injury Patients in a Rehabilitation Unit

Abstract: There is a high prevalence of SWCD in CHI patients admitted to a brain injury rehabilitation unit. Patients with SWCD have longer stays in both acute and rehabilitation settings and may be a marker for more severe injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 22 publications
5
60
0
1
Order By: Relevance
“…Natalie Grima, DPsych 1,2,4 ; Jennie Ponsford, PhD 2,4 ; Shantha M. Rajaratnam, PhD 4,5,6 ; Darren Mansfield, MD, PhD 3,4 was hypothesized that those with TBI would display widespread objective and subjective sleep deficits as compared to controls without head injury. The present study aimed to summarize current literature, which would identify important avenues for future research.…”
Section: Sleep Disturbances In Traumatic Brain Injury: a Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Natalie Grima, DPsych 1,2,4 ; Jennie Ponsford, PhD 2,4 ; Shantha M. Rajaratnam, PhD 4,5,6 ; Darren Mansfield, MD, PhD 3,4 was hypothesized that those with TBI would display widespread objective and subjective sleep deficits as compared to controls without head injury. The present study aimed to summarize current literature, which would identify important avenues for future research.…”
Section: Sleep Disturbances In Traumatic Brain Injury: a Meta-analysismentioning
confidence: 99%
“…1 Although a large majority of people with TBI generally make a good physical recovery, disrupted sleep can often go untreated, impacting quality of life, impeding rehabilitation and return to pre-injury activities. [2][3][4][5] Our recent work showed significant interrelationships between daytime sleepiness, daytime fatigue, cognitive impairment, and mood disturbances in TBI. 6 While individuals with TBI are known to report sleep problems, 1 the specific changes to sleep remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Injury-related damage to sleep-wake regulating centers and associated pathways or neurotransmitter systems is implicated as the cause of such disturbances. 5,11,14 Anxiety and depression that frequently follow TBI are also likely contributing factors. 10,15 From the School of Psychology and Psychiatry (J.A.S., D.L.P., J.R.R., J.P.-N., J.L.P., S.M.W.R.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Reported sleep complaints include insomnia, hypersomnolence, and altered sleep-wake cycles. 7 Understanding of changes to sleep following TBI is limited.…”
mentioning
confidence: 99%
“…Makley et al found that length of stay in acute care increased risk of having sleep wake cycle disturbance and a total prevalence of 68 percent. Presence of sleep disruptions also predicted longer required stay in the rehabilitation center [65]. The second study utilized actigraphy measurements taken for seven consecutive days on a moderate to severe TBI sample, with measurements begun within the first 72 h after admission to a rehabilitation facility.…”
Section: Acute Phase (0-3 Months)mentioning
confidence: 99%